Evaluación de diferentes porcentajes de tusa de maíz, afrecho de trigo y soya en la alimentación de cerdos de engorde - Lema Analuisa, Marco Andrés (2019)
In this investigation 3 diets were evaluated with different percentages of corn cob, wheat bran and soy in the feed of pigs in the fattening stage, so we set out to evaluate the diets with the different percentages in the fattening stage to determine the best treatment (diet) supplied to the pigs; analyze the bromatological properties, the best treatment that is part of the diet and finally establish the cost-benefit ratio in order to perform an economic analysis of the diets provided. For the present investigation, the experimental design that was used was a completely randomized blocks design (DBCA) with 4 treatments and 7 repetitions, with a total of 28 experimental units, Landrace pigs of 2 months of age with an initial average weight of 37 kg. The experimental results showed significant statistical differences during the fattening stage, where it was observed that at least one of the percentages of corn cob, wheat bran and soybeans, had significant effects during the fattening stage. Based on the results obtained, we can recommend the T3 diet, 65% corn cob meal + 30% wheat bran + 5% soy flour, which had the best results with a final average weight of 81,2 kg. Through a bromatological analysis we determined the properties of the treatment with the highest digestibility (T3) and we obtained its percentages, protein 12.8%, humidity 16,3%, ash 7,6%, fat 3,7%, fiber 12,9%, starch 20,4%, thus we could determine that the Diet with greater adaptation was that of treatment three (T3) with a total weight gain of 44Kg.